Autophagy and Skeletal Muscles in Sepsis - Mofarrahi, Mahroo; Sigala, Ioanna; Guo, Yeting; Godin, Richard; Davis, Elaine C.; Petrof, Basil; Sandri, Marco; Burelle, Yan; Hussain, Sabah N. A. (PLOS ONE, 2012)
Background Mitochondrial injury develops in skeletal muscles during the course of severe sepsis. Autophagy is a protein and organelle recycling pathway which functions to degrade or recycle unnecessary, redundant, or inefficient cellular components. No information is available regarding the degree of sepsis-induced mitochondrial injury and autophagy in the ventilatory and locomotor muscles. This study tests the hypotheses that the locomotor muscles are more prone to sepsis-induced mitochondrial injury, depressed biogenesis and autophagy induction compared with the ventilatory muscles. Methodology/Principal Findings Adult male C57/Bl6 mice were injected with i.p. phosphate buffered saline (PBS) or E. coli lipopolysaccharide (LPS, 20 mg/kg) and sacrificed 24 h later. The tibialis anterior (TA), soleus (SOLD) and diaphragm (DIA) muscles were quickly excised and examined for mitochondrial morphological injury, Ca++ retention capacity and biogenesis. Autophagy was detected with electron microscopy, lipidation of Lc3b proteins and by measuring gene expression of several autophagy-related genes. Electron microscopy revealed ultrastructural injuries in the mitochondria of each muscle, however, injuries were more severe in the TA and SOL muscles than they were in the DIA. Gene expressions of nuclear and mitochondrial DNA transcription factors and co-activators (indicators of biogenesis) were significantly depressed in all treated muscles, although to a greater extent in the TA and SOL muscles. Significant autophagosome formation, Lc3b protein lipidation and upregulation of autophagy-related proteins were detected to a greater extent in the TA and SOL muscles and less so in the DIA. Lipidation of Lc3b and the degree of induction of autophagy-related proteins were significantly blunted in mice expressing a muscle-specific IκBα superrepresor. Conclusion/Significance We conclude that locomotor muscles are more prone to sepsis-induced mitochondrial injury, decreased biogenesis and increased autophagy compared with the ventilatory muscles and that autophagy in skeletal muscles during sepsis is regulated in part through the NFκB transcription factor.